PENGARUH MANAJEMEN KELAS TERHADAP KONSENTRASI BELAJAR SISWA SEKOLAH DASAR - Ayesha Raudhatuzzahra; Nurhidayati; Barep Hapit Surya Putra (STKIP Subang, 2026)
This research is motivated by the low level of student concentration at MI Imam Puro, which is characterized by students being easily distracted and showing low participation during the learning process. This condition is also influenced by diverse student backgrounds, including those from boarding schools with high study loads. The purpose of this study is to describe classroom management, determine the level of learning concentration, and analyze the influence of classroom management on the learning concentration of 3rd-grade students at MI Imam Puro. This study uses a quantitative approach with a survey method and an ex-post facto design. The sample consisted of 20 students selected through purposive sampling. Data were collected using questionnaires and analyzed using simple linear regression. The results showed that classroom management is in the moderate category (45%), while student concentration is in the high category (55%). The hypothesis test results show a significance value of 0.016 (< 0.05), indicating a positive and significant influence of classroom management on learning concentration. The coefficient of determination (R Square) is 0.281, which means classroom management contributes 28.1% to student concentration, while the remaining 71.9% is influenced by other factors. The regression equation formed is Y = 27.201 + 0.371 X. Thus, effective classroom management by teachers is a key factor in increasing students' focus and involvement in elementary school.